ANALISIS KINERJA BIDANG KEBUDAYAAN DINAS KEBUDAYAAN DAN PARIWISATA KOTA SEMARANG (Penanganan Lunturnya Nilai-Nilai Budaya Masyarakat di Kota Semarang) - Sarwo Edi; Dyah Hariani (Journal of Public Policy and Management Review, 2017)
The era of globalization, the erosion of local culture in Indonesia, declining interest and public concern Semarang city of art and culture, and performance Cultural Affairs D.C.T Semarang into the background in this study. The research objective to analyze the performance of Cultural Affairs D.C.T Semarang and describe the factors supporting and inhibiting performance of Cultural Affairs D.C.T Semarang in dealing with the erosion of cultural values of the people in the city of Semarang. This study uses the theory of organizational performance with five dimensions of organizational performance namely productivity, quality of service, responsiveness, responsibility, and accountability, while also enabling and inhibiting factors are derived from the internal and external environments. The approach used qualitative descriptive. The technique of collecting data through interviews, documentation, and literature study with employees of Cultural Affairs D.C.T informant Semarang. The results showed that the performance of Cultural Affairs D.C.T Semarang in handling the erosion of cultural values of the people in the city of Semarang can be said is good, but not yet maximal because there are constraints on the dimensions of productivity and quality of service that is the lack of coordination and cooperation and the lack of community participation. Supporting factors such as the objectives in the Strategic Plan 2010-2015 D.C.T Semarang year, the organizational structure is very good, quality human resources, the attitude of discipline and mutual cooperation, RPJMD policy, economic conditions and their budgets, community participation when a big event, and public criticism and suggestions. While the inhibiting factors that limited human resources, regulations, central and local government is so strict about the grant, the absence of authority in the national film industry, certification of cultural heritage, and preservation of the Java language, limited budget, and lack of participation, interest and public awareness to conservation culture. Suggested of Cultural Affairs can improve productivity, maximize cooperation has been established, adding cooperation networks, and coordinate with the Central Government and R.E.A Semarang.